Developing teaching and learning in Africa : decolonising perspectives - Msila, Vuyisile (African Sun Media, 2020)
Developing Teaching and Learning in Africa is a collection of chapters that carry on the topical discussions on Indigenous knowledges and western epistemologies. African societies still aspire towards knowledge that is liberatory, enhance critical thinking and decentre Eurocentrism. The contributors explore these decolonial debates as they navigate ways of moving towards epistemic freedom and cognitive justice.